THE EFFECT OF Trichuris muris EGG ON THE GOBLET CELLS IN INTESTINE OF MICE (MUS MUCULUS) - Lulu Hasna Ulfadila; Ahmad Husairi; Istiana Istiana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Goblet cells are the immune response in the intestinal epithelium to produce mucus as a defense digestive tract mucosa caused by Trichuris muris infestation. The study purpose was to analyze the effect Trichuris muris towards goblet cells number in mice’s intestine. This research was a true experimental with the posttest control group design. The subjects were 30 male mice types BALB / c which 2 months old with an average weight 20-30 gram. Samples were taken by simple random sampling. Mice divided into a control group, low-dose group (40 worm eggs) and high-dose groups (200 worm eggs) observed for 30 days and then counted the goblet cells number in each preparation. The data analysis was tested by shapiro wilk test and one-way ANOVA and continued by post hoc test. The results demostrated the average value of the goblet cells number in the control group, low-dose and high dose increased by higher dose worm eggs and had the value (p =< 0.05). This described there were Trichuris muris’s eggs inflluence towards the goblet cells number in mice (Mus musculus). Keywords: Trichuris muris, mice (Mus musculus), goblet cells in intestinum